Human resource management problems over the life cycle of small to medium‐sized firms - Rutherford, Matthew W.; Buller, Paul F.; McMullen, Patrick R. (Human Resource Management, 2003)
AbstractThis study uses a sample of 2,903 small to medium‐sized firms to examine the manner in which HR problems vary over the organizational life cycle. We found that a four‐stage model was appropriate. Interestingly, firm age did not emerge as a significant indicator of stage—the firms' HR problems varied across stages defined by growth. Training problems were highest in high‐growth firms and lowest in low‐growth firms; compensation problems were highest in moderate‐growth firms and lowest in high‐growth firms; and recruiting problems were highest in no‐growth firms and lowest in low‐growth firms. © 2004 Wiley Periodicals, Inc.